Pengaruh Kemampuan Interpersonal, Modal Psikologi, dan Dukungan Supervisor Terhadap Kinerja Tenaga Penjualan - Wulandari Wulandari; Reny Nuraini; Fadillah Maghfiroh; Didit Darmawan; Siti Nur Halizah; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to examine how three factors, namely interpersonal skills, psychological capital, and supervisor support influence the performance of salespeople in a business. In an increasingly competitive business environment, these factors are considered to have a crucial role in shaping individual performance in the sales team. The research method used is quantitative. Questionnaires are used to measure interpersonal skills, psychological capital, supervisor support, and salesperson performance. The collected data can then be analyzed using statistical techniques such as multiple linear regression to examine the influence of the research variables. The results of the data analysis show that interpersonal skills have a significant influence on salesperson performance. This emphasizes the importance of communication skills, building positive relationships, and managing social interactions in achieving successful sales results. Furthermore, psychological capital also has a significant impact on salesperson performance. Psychological factors such as self-confidence, motivation, and psychological well-being can motivate and encourage salespeople to achieve targets and overcome obstacles better. In addition, the findings also show that the support provided by supervisors has a significant effect on salesperson performance. Support in the form of clear directions, and emotional support from supervisors can motivate and assist salespeople in achieving set sales goals